2006
DOI: 10.1021/jm060917u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Metabotropic Glutamate Receptor Activity of S-Oxidized Variants of (−)-4-Amino-2-thiabicyclo-[3.1.0]hexane-4,6-dicarboxylate:  Identification of Potent, Selective, and Orally Bioavailable Agonists for mGlu2/3 Receptors

Abstract: (-)-4-Amino-2-thiabicyclo-[3.1.0]hexane-4,6-dicarboxylate (LY389795, (-)-3) is a highly potent and selective agonist of metabotropic glutamate receptors 2 (mGlu2) and 3 (mGlu3). As part of our ongoing research program, we have prepared S-oxidized variants of (-)-3, compounds (-)-10, (+)-11 (LY404040), and (-)-12 (LY404039). Each of these chiral heterobicyclic amino acids displaced specific binding of the mGlu2/3 receptor antagonist 3H-2S-2-amino-2-(1S,2S-2-carboxycycloprop-1-yl)-3-(xanth-9-yl)propanoic acid (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
43
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 42 publications
2
43
0
Order By: Relevance
“…We report here that LY404039 effectively modulates mGlu2/3 receptors in situ with a potency similar to that previously reported for LY354740, suggesting that this compound should also demonstrate efficacy in animal models of psychosis and anxiety. Perhaps most importantly, we demonstrate here that despite the in vitro similarities between LY354740 and LY404039, oral administration of LY404039 results in much higher plasma levels and bioavailability (63%; Monn et al, 2007) than previously observed following oral administration of LY354740 (ϳ10%; Johnson et al, 2002) and a different pharmacokinetic profile. The mechanism by which LY404039 crosses the gastrointestinal tract is not clearly understood.…”
mentioning
confidence: 45%
See 2 more Smart Citations
“…We report here that LY404039 effectively modulates mGlu2/3 receptors in situ with a potency similar to that previously reported for LY354740, suggesting that this compound should also demonstrate efficacy in animal models of psychosis and anxiety. Perhaps most importantly, we demonstrate here that despite the in vitro similarities between LY354740 and LY404039, oral administration of LY404039 results in much higher plasma levels and bioavailability (63%; Monn et al, 2007) than previously observed following oral administration of LY354740 (ϳ10%; Johnson et al, 2002) and a different pharmacokinetic profile. The mechanism by which LY404039 crosses the gastrointestinal tract is not clearly understood.…”
mentioning
confidence: 45%
“…Interestingly, although similar to LY354740, LY404039 was ϳ2-to 3-fold less potent in this assay. Despite the slightly lower potency of LY404039 versus LY354740 in binding and functional assays, LY404039 demonstrated higher plasma exposure and better oral bioavailability in pharmacokinetic experiments in rats [ϳ63% (see Monn et al, 2007) compared with ϳ10% for LY354740 (Johnson et al, 2002)]. Electrophysiological studies indicated that LY404039 suppressed electrically evoked excitatory activity in the striatum, an effect reversed by the mGlu2/3 receptor antagonist LY341495, indicating that the suppression of neural activity was probably mediated via mGlu2/3 receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid analog LY404039 (Monn et al, 2007) is a potent and highly selective agonist for group II mGlu receptors, and it has no appreciable affinity for group I or group III mGlu receptors, ionotropic glutamate receptors, glutamate transporters, or other receptors such as dopamine and serotonin (Rorick-Kehn et al, 2007a). Like atypical antipsychotics (e.g., clozapine and olanzapine), LY404039 displays antipsychotic-like effects in animal models of psychosis.…”
mentioning
confidence: 99%
“…Like atypical antipsychotics (e.g., clozapine and olanzapine), LY404039 displays antipsychotic-like effects in animal models of psychosis. LY404039 reverses phencyclidine (PCP)-induced hyperlocomotion in rats in a dose-dependent manner (Monn et al, 2007;Rorick-Kehn et al, 2007b). Although LY404039 has no affinity at dopamine receptors, it attenuates the locomotorstimulating effects of d-amphetamine (AMP).…”
mentioning
confidence: 99%